EFEKTIVITAS PENEMPATAN PEGAWAI NEGERI SIPIL DI DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN BANYUASIN - Sahirrudin Sahirrudin (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
Employees are the driving force of the organization to realize its functions and achieve predetermined goals. At this time when the perceived challenges are getting more and more complex, the desire of public organizations to increase competitiveness demands to improve the quality of employees who are proactive to any turmoil and change. Thus, it can be said that the success of an organizational goal is very much dependent on the man behind the gun.This study used quantitative research approach with the level of descriptive explanation. The method used in sampling is a method of sampling of cencus or total anumeration complete the data collection method that takes each element of the population or characteristics present in the population. So the sample in this study are all permanent employees or the Civil Service Revenue Office For Management of Regional Revenue, Finance and Assets Banyuasin District until 2013. That as many as 37 people. Data used in this reseach is the primary data and secondary data. While data collecting techinque done with the method of questionnaire, observation and documentation. The data analysis techique is done by using descriptive statistical calculations. Such data can be tested by determining the answers in the questionnaire scores, where scores were divided into 4 categories, using a likert scale, to determine whether whether the placement of human resources in the Revenue DPPKAD Banyuasin District classified as very affective, effective, ineffective or very ineffective. The results showed that the placement of human resources in the Revenue Office For Management of Regional Revenue. Finance and assets Banyuasin district, including in the category overall quite effective. It is seen from the weights for the overall indicator is based on the gradation of 102.7 which made the score showed that the level of effective of the placement of human resources in the Revenue Office For Management of Regional Revenue, Finance and Assets Banyuasin Regency effective in a category, indicators used in research on the effectiveness of placments in the Revenue Office For Management of Regional Revenue,  Finance and Assets Banyuasin consists of four indicators namely Morality, aggression, leadership, and human relations.